2023
DOI: 10.21315/mjms2023.30.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stromal Cells Derived from Perinatal Tissues: Sources, Characteristics and Isolation Methods

Abstract: Mesenchymal stromal/stem cells (MSCs) derived from perinatal tissues have become indispensable sources for clinical applications due to their superior properties, ease of accessibility and minimal ethical concerns. MSCs isolated from different placenta (PL) and umbilical cord (UC) compartments exhibit great potential for stem cell-based therapies. However, their biological activities could vary due to tissue origins and differences in differentiation potentials. This review provides an overview of MSCs derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) are pluripotent stem cells that can be derived from a variety of tissues, including bone marrow, adipose, human umbilical cord blood, and others. 12,13 MSCs have the capacity for multidirectional differentiation and self-renewal, and they can differentiate into end-stage cells such as lipogenic cells, chondrogenic cells, and neuronal cells in vitro when subjected to various stimulating factors and induction media. [14][15][16] These qualities have caused MSCs to gradually gain attention in the fields of medicine and tissue engineering in recent decades, and numerous experiments have now demonstrated that MSCs are a very promising research area and have extensive research significance for the regeneration of various tissues and cells, such as bone, skin, and nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are pluripotent stem cells that can be derived from a variety of tissues, including bone marrow, adipose, human umbilical cord blood, and others. 12,13 MSCs have the capacity for multidirectional differentiation and self-renewal, and they can differentiate into end-stage cells such as lipogenic cells, chondrogenic cells, and neuronal cells in vitro when subjected to various stimulating factors and induction media. [14][15][16] These qualities have caused MSCs to gradually gain attention in the fields of medicine and tissue engineering in recent decades, and numerous experiments have now demonstrated that MSCs are a very promising research area and have extensive research significance for the regeneration of various tissues and cells, such as bone, skin, and nerves.…”
Section: Introductionmentioning
confidence: 99%